Mexico : Financial Sector Assessment Program Update; Technical Note; Risk Management Practices and Stress Tests of Commercial Banks, The Insurance Sector, and the Derivatives Exchange. (IMF Staff Country Reports; Country Report, 2007)
This technical note on Mexico's Financial Sector Assessment Program update presents an overview of the risk management practices and stress test results carried out for the Mexican commercial banks and the insurance sector. The stress test results include the reporting of scenario analyses undertaken as part of the Mexico Financial System Assessment Program update to help in the assessment of the resilience of the financial system to a set of key risks. These scenarios complement other risk management practices such as liquidity risk and contagion analysis carried out by the relevant supervisors.